Installing Islamic Art: Interior Space and Temporal Imagination. (1st July 2018) - Kadoi, Yuka
This special issue challenges the anachronistic image of Islamic art galleries that dominated the museum field worldwide during the twentieth century and seeks alternative modes of display to suit current sociopolitical circumstances. Entitled 'Installing Islamic Art: Interior Space and Temporal Imagination', the present issue gathers articles dealing with multifaceted topics that address the issue of display and curation of 'Islamic art'. While the term itself requires further critical reassessment, each author offers an innovative approach and methodological proposition in an effort to recontextualize the current exhibitory trends in the public presentation of material remains from Muslim-majority societies, including the Arab lands, Iran, Turkey, and South Asia. Taken together, this collection of articles reveals many possibilities, rather than limitations, regarding how to thoughtfully showcase Muslim cultural heritage, representing a positive indication of future of curating Islamic art.